LOCAL RELAXATION AROUND [6]CR3+ IN SYNTHETIC PYROPE-KNORRINGITE GARNETS, [8]MG3 [6] (AI1-XCRX 3+)2 [4]SI3O12, FROM ELECTRONIC ABSORPTION SPECTRA - Taran M.N.; Platonov A.N.; Langer K.; Abs-Wurmbach I.; Frost D.J. (My University, 2004)
Pyrope-knorringite garnets, Mg3(Al1-X Cr3+X)2Si3O12 with X=0.25, 0.50, and 1.00, were synthesized between 9 and 16 GPa and 1300 and 1600 °C, using multianvil high-pressure techniques. The garnets with X=0.25 and 0.50 are fine-grained, pink and violet in color. The end-member knorringites with X=1.00 are black when compact and gray when coarse-grained. The fine powder is greenish gray in natural light and pale pink under a tungsten lamp. Powder remission spectra in the wavenumber range 30 000–10 000 cm−1 on finely powdered crystals were measured by two different methods: (I.) by the use of a small integrating sphere for small samples or (II.) microscope-spectrometric measurement using diffusely reflected radiation from a 45° illuminated microsample. Both methods yielded similar diffuse reflectance spectra. The following crystal-field parameters of [6]Cr3+ were determined for garnets with X=0.25, 0.50, 1.00: 10 Dq=17 856, 17 596, 17 286 cm−1; and B=654, 677, 706 cm−1; nephelauxetic ratio β=(B field/B free)= 0.71, 0.74, 0.77. The β-values indicate decreasing covalency of the Cr–O bond with increasing Cr content. The 10 Dq value for together with the mean Cr–O distance in end-member knorringite, 1.96 Å (Novak and Gibbs 1971), were used to calculate from the spectral data, local mean Cr–O distances (Langer 2001a) as a function of composition. The results indicate relatively strong local site relaxation with a value of ɛ=0.77.